Q. 44.9( 10 Votes )

# Using the identit

Answer :

Given the identity

(a +b)^{2} = a^{2} + 2ab + b^{2}

(i) (a + 6)^{2}

Using the given identity

Here a = a, b = 6

= a^{2} +2 × a × 6 +6^{2}

= a^{2} +12a +36

(ii) (3x + 2y)^{2}

Using the given identity

Here a = 3x, b = 2y

= (3x)^{2} + 2 × 3x × 2y +(2y)^{2}

= 9x^{2} + 12xy +4y^{2}

(iii) (2p + 3q)^{2}

Using the given identity

Here a = 2p, b = 3q

= (2p)^{2} +2× 2p × 3q + (3q)^{2}

= 4p^{2} + 12pq +9q^{2}

(iv) (x^{2} + 5)^{2}

Using the given identity

Here a = x^{2}, b = 5

= (x^{2})^{2} +2 × x^{2} × 5 +5^{2}

= x^{4} + 10x^{2} +25

Rate this question :

Find the product:Karnataka Board - Mathematics Part I

If a, b are ratioKarnataka Board - Mathematics Part I

Use the identity Karnataka Board - Mathematics Part I

Express the folloKarnataka Board - Mathematics Part I

Find the product:Karnataka Board - Mathematics Part I

Simplify:

Find the product:Karnataka Board - Mathematics Part I

Find the product:Karnataka Board - Mathematics Part I

Evaluate these usKarnataka Board - Mathematics Part I

Find the product:Karnataka Board - Mathematics Part I